Feet training in young elite handball players: a step forward? - Buchheit, M.; Parisy, A.; Leblond, F.; Renaud, C. (Sport Performance & Science Reports, 2017)
Acceleration, change of direction (COD) speed and jumping abilities are among the most important physical traits for successful participation at the elite level in many team sports (1-4). In addition to muscle fiber types, morphological characteristics and optimal running/jumping technique, there is a common belief that feet strength and flexibility are key factors for appropriate running propulsion and/or jumping impulsion (5-7). There is, however, limited scientific evidence to support this empirical belief, and whether feet efficiency could be trained remains also unclear. Aim. The aim of the present study was to examine the effect of a specific feet training program on acceleration, change of direction speed, jumping abilities and high-intensity intermittent performance (including CODs) in young elite handball players